The normal tax treatment of cross-border dealings between various parts of a company in terms of the Income Tax Act, No. 58 of 1962, compared to selected aspects of the Organisation for Economic Cooperation and Development's Model convention on incom - Hattingh, Petrus Johannes (Department of Commercial Law, 2014)
Includes bibliographical references (leaves 147-151).